1975
DOI: 10.1017/s0003356100035042
|View full text |Cite
|
Sign up to set email alerts
|

Ground roughage in the diet of the early-weaned calf

Abstract: An experiment was conducted with 60 male Friesian calves between 5 and 11 weeks of age. The experiment was a 5 x 2 x 2 factorial design. The five major treatments were the inclusion of 20 or 40 % ground wheat straw or 20, 40 or 60 % ground lucerne in a pelleted diet. A methane inhibitor was included in the diet given to 30 of the calves. The diets were given alone or with a chaffed wheat straw supplement ad libitum. All diets contained 2% sodium bicarbonate. The weight gain of the calves was greater with the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
2
2

Year Published

1978
1978
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 26 publications
(27 reference statements)
2
14
2
2
Order By: Relevance
“…Amicloral tended to decrease molar proportions of acetic acid and to increase butyric acid, but it had no effect on propionic acid, which is in agreement with previous reports Trei et al, 1972). While some workers have shown increased molar proportions of propionate with amicloral (Leibholz, 1975), there are several reports of adaptation to the additive, with responses diminshing with time Clapperton, 1977). Trei et al (1972) collected rumen fluid after 7 and 90 days and reported respective changes in propionate of 44 and 10% and in butyrate of 18 and 63%.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Amicloral tended to decrease molar proportions of acetic acid and to increase butyric acid, but it had no effect on propionic acid, which is in agreement with previous reports Trei et al, 1972). While some workers have shown increased molar proportions of propionate with amicloral (Leibholz, 1975), there are several reports of adaptation to the additive, with responses diminshing with time Clapperton, 1977). Trei et al (1972) collected rumen fluid after 7 and 90 days and reported respective changes in propionate of 44 and 10% and in butyrate of 18 and 63%.…”
Section: Resultssupporting
confidence: 92%
“…Lower (P<.05) concentrations of ruminal VFA in steers fed amicloral (table 3) (1972) and Leibholz (1975), who suggested that lower VFA may have reflected reduced ruminal microbial fermentation. However, Van Der Walt (1977) has shown that single samples of total VFA concentrations are not reliable estimates of total 24-hr VFA production rates, and the higher crude fiber digestibility in this trial indicates that the extent of fermentative digestion was not compromised by amicloral.…”
Section: Resultsmentioning
confidence: 98%
“…in dairy calves, whereas others reported negative effects of forage addition on starter feed intake (Hibbs et al, 1956;Whitaker et al, 1957;Leibholz, 1975;Hill et al, 2008). In the current study, alfalfa hay feeding did not negatively affect starter feed intake compared with control calves, indicating that metabolic rather than physical factors regulate feed intake at low levels of forage inclusion (Tafaj et al, 2007).…”
Section: Calf Healthcontrasting
confidence: 41%
“…Regardless of PS, the effects of forage feeding to dairy calves on feed intake are not conclusive. Several studies (Kincaid, ; Thomas and Hinks, ; Stobo et al., ; Khan et al., , ) described that forage feeding increased starter feed consumption in dairy calves, whereas others reported negative effects of forage addition on starter feed intake (Hibbs et al., ; Whitaker et al., ; Leibholz, ; Hill et al., ). In the current study, alfalfa hay feeding did not negatively affect starter feed intake compared with control calves, indicating that metabolic rather than physical factors regulate feed intake at low levels of forage inclusion (Tafaj et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Algunos estudios concluyen que la adición de forraje aumenta el consumo de materia seca proveniente del alimento balanceado (Kincaid 1980, Thomas y Hinks 1982, Stobo et al 1985. Sin embargo, otros han demostrado un impacto negativo y recomiendan no utilizarlo (Leibholz 1975). En el presente estudio, los animales del tratamiento harina+forraje, consumieron en promedio 200 g/d de forraje verde después de la tercera semana y hasta las ocho semanas de edad.…”
Section: Consumo De Alimentounclassified